Pore Size Distribution Controls Dynamic Permeability - Li, Jimmy X.; Rezaee, Reza; Müller, T.M.; Sarmadivaleh, Mohammad (AMER GEOPHYSICAL UNION, 2021)
Probing the flow permeability of porous media with elastic waves is a formidable challenge, also because the wave-induced oscillatory motion renders the permeability frequency dependent. Existing theoretical models for such a dynamic permeability assume that the frequency dependence is primarily controlled by a single characteristic length scale of the pore space. However, the fact that in most natural porous media there exists a distinct range of pore sizes is ignored. To overcome this limitation, we develop a dynamic permeability model that explicitly incorporates the pore size distribution. We show that the pore size distribution has a first-order effect on the dynamic permeability. Since the pore size distribution can be deduced from techniques such as nuclear magnetic resonance, our results indicate the possibility to jointly use remote-sensing technologies for improved permeability determination and cross-fertilization of laboratory and in-field techniques.